Reconstructing Paylater Schemes in Islamic Fintech: A Normative Analysis of Deferred Payment Contracts Under Sharia Economic Law - Hayati, Anisah Norlaila; Fitrianoor, Wahyu; Saliro, Sri Sudono; Fadillah, Nor; Pane, Siti Rif’atussa’adah Sitorus (Syariah: Jurnal Hukum dan Pemikiran, 2025)
The proliferation of financial technology (fintech) innovations has reshaped consumer behavior through digital payment models such as paylater, enabling deferred payments in online transactions. Despite its practical benefits, the paylater mechanism raises legal and ethical concerns in Islamic economic law due to possible elements of riba (usury), gharar (uncertainty), and contractual ambiguity. This study investigates the normative validity of paylater schemes within the framework of Sharia economic law by reconstructing them through Sharia-compliant contractual models. Using a normative-juridical method supported by doctrinal analysis, this research examines primary sources such as the Compilation of Sharia Economic Law (KHES), relevant fatwas of the National Sharia Council–Indonesian Ulema Council (DSN-MUI), and international Sharia standards (AAOIFI and IFSB), supplemented by secondary literature on Islamic finance and e-commerce. The findings indicate that paylater is permissible under Sharia when structured as bai‘ bi tsaman ajil (deferred payment sale) or murabahah (cost-plus sale), provided that price, ownership, and risk are clearly defined and that penalties do not involve interest. Conversely, a paylater model based on qardh (loan) with fixed returns constitutes riba and violates Islamic principles. The study further offers practical recommendations for regulators and fintech operators to design transparent, fair, and Sharia-compliant digital financing systems aligned with maqāṣid al-sharī‘ah to protecting religion, life, intellect, wealth, and lineage. This reconstruction contributes to the global discourse on Islamic fintech by proposing a viable Islamic “Buy Now Pay Later” (BNPL) model that balances consumer protection, market competitiveness, and ethical finance.